ANALISIS PENGARUH KEBIJAKAN PEMERINTAH TERHADAP NILAI TUKAR RUPIAH SETELAH KRISIS EKONOMI GLOBAL 2008 - Dwita Sakuntala (Universitas Negeri Medan, 2018)
At the end of 2008 there was a financial crisis in America that impacted the global economy including Indonesia. This condition causes the movement of the rupiah to weaken following the global economy. The weakening of the rupiah causes, the economic conditions in Indonesia participate weakened. This study aims to determine the effect of money supply, gross domestic income, inflation and interest rates on the rupiah against the US dollar after the 2008 global economic crisis.The basic theory used in this research is the monetary approach theory was developed by Frenkel (1984). The analysis model used is ARCH/GARCH model with Maximum Likelihood estimation method. The empirical result of these research shows that the variable which have positive and significant influence is variable of money supply, and interest rates. Real GDP have negative and significant influence to the exchange rate. While inflation has no effect.